Total synthesis of Cinncassin A1. (7th April 2020) - Nuriye, Ahmed Y.; Craescu, Cristina V.
Abstract: In this communication, we report the first total synthesis of the phenolic natural product Cinncassin A1, which was recently isolated from the twigs of the cinnamon plant ( Cinnamomum cassia ). The novel and concise synthesis strategy involves a highly diastereoselective titanium enolate homocoupling and a permanganate‐mediated oxidative lactonization reaction as key steps. The structure of the compound was verified by single‐crystal X‐ray crystallography. Abstract :